Single crystals of organometal trihalide perovskite : synthesis and optoelectronic properties - Nguyen, Huy Tiep (2019)
Over the last ten years, organic lead trihalide perovskites (CH3NH3PbX3, X=Cl, Br, I) have demonstrated to be the most potential material in electronic and photonic applications due to its unique properties including high absorption coefficient,1 low intrinsic recombination rates,2 ambipolar transportation,3 and long carrier diffusion lengths.4 Perovskite materials have been intensively studied for numerous applications such as solar cells,5-13 photodetectors.14-16 light-emitting diodes,17,18 and lasing,19,20 In the photovoltaic cell viewpoint, since the first perovskite solar cell (PSC) report in 2009 with a power conversion efficiency (PCE) of 3.8% only,21 the best PSC has recently achieved a surprisingly efficiency up to 23%,13 which fulfilled the commercial standard for the outside solar cell. However, the major drawback of perovskite materials is the moisture instability which limited them for being launched to the commercial market. In that critical situation, the single crystal has promised to enable the perovskite solar cells to break through their limitations. More and more reports have shown that the perovskite single crystal helped to suppress the charge recombination and prevent the bulk defect density, leading to higher PCE and longer stability.22-25 The changing of alkylammonium chains from the CH3NH3 to hydrophobic longer chains such as C6H5C2H4NH3 has been demonstrated to enhance the stability of perovskites.26 Beside the instability issue, the environmental concern about the lead content has been a consideration. However, unlike traditional PSCs based on spin coating or dip coating polycrystal thin films, the single crystal one has been difficult to synthesize due to the lack of the sufficient growth crystallization methods. This thesis shows the results for single crystals growth of large centimeter scaled 3D CH3NH3PbX3, and 2D layered (C6H5C2H4NH3)2MX3 (X = I, Br, Cl; M = Pb, Cu) perovskite single crystals by solution crystallization methods. Their crystalline, electronic, optical, phase transition and magnetic properties have been also introduced. The results should be useful for investigation of novel applications based on the stable and high-performance perovskite single crystals.